2023
DOI: 10.1021/acsanm.3c02000
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Assisted Transfer of Graphene for Efficient Hydrogen Isotope Separation

Abstract: Graphene has been shown to act as an efficient sieve for hydrogen isotope separation since the perfect monolayer graphene is impermeable to almost all atoms and molecules but permeable to protons. Large-area graphene films can be produced by chemical vapor deposition (CVD) and exhibit a considerably high proton−deuteron separation factor of ∼8. However, the performance of the graphene-based membrane is often limited by the presence of cracks and imperfections introduced mainly during the transfer process. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…A similar strategy was adopted by Shen et al in the water-assisted-transfer of MoS 2 , while PDMS/PMMA/Cu was used as the carrier film . Besides Cu, Au, palladium (Pd), and Ni , are also reported as supporting layers in metal-assisted transfer. However, although polymer residues can be avoided, metal/metal oxide particles and metal ions are introduced in these transfer methods due to the use of metal and metal etchant.…”
Section: Clean Transfer Methodsmentioning
confidence: 99%
“…A similar strategy was adopted by Shen et al in the water-assisted-transfer of MoS 2 , while PDMS/PMMA/Cu was used as the carrier film . Besides Cu, Au, palladium (Pd), and Ni , are also reported as supporting layers in metal-assisted transfer. However, although polymer residues can be avoided, metal/metal oxide particles and metal ions are introduced in these transfer methods due to the use of metal and metal etchant.…”
Section: Clean Transfer Methodsmentioning
confidence: 99%
“…The electrochemical bubbling method offers a superior alternative to wet etching for transferring graphene (Figure f), effectively bypassing the need to etch the metal substrate, which traditional methods fail to fully cleanse of minute metal particles that could modify graphene’s electrical traits. , This technique entails spin-coating PMMA on a graphene/conductive substrate, immersing it in an electrolytic cell with the PMMA side as the cathode and a platinum anode. An external voltage triggers electrolysis, producing hydrogen bubbles that lift the PMMA/graphene layer from the substrate .…”
Section: Sensing Channel Of Gfet Biosensormentioning
confidence: 99%
“…7 An and collaborators 9 calculated that the barrier value of proton penetration that passes through the lattice center ring of 7MRs of topological Stone−Wales defect was already as low as 1 eV, and the selectivity of H + -over-D + was 7 at room temperature. Wang et al 29 fabricated a Pd/Graphene/Nafion composite membrane to conduct experiments on proton−deuterium separation and found that the membrane provided a proton− deuterium separation factor of up to 9.7, paving the way for the preparation of large-area graphene-based composite membranes. Zeng et al 30 experimented with a new method for the rapid separation of hydrogen and helium by electrochemical hydrogen pump (EHP) and found that proton conduction in the catalyst layer and proton exchange membrane became the speed-controlling step of the process but did not describe the specific mechanism.…”
Section: Introductionmentioning
confidence: 99%